Shirking or mismatch? Coach-team separation in German professional soccer - Nikolaus Hautsch; Erik Lehmann; Susanne Warning; Bernd Frick (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 2001)
Some authors suggest that firing a coach reflects a principal-agent problem between team managers and coaches. Another explanation emphasizes the matching problem between teams and coaches. This paper provides empirical evidence for the latter: Using German soccer league data, we analyze the determinants of coach dismissals in terms of the impact of a team's performance on the probability to be fired. It is shown that the probability for a coach dismissal increases over time.
Keywords: 330